Chemical Effectiveness of a Natural Deodorant Spray Formulated with Basil Leaf Extract and Lemon Extract as Antibacterial Agents - Nadia Mubarokah; Anisa Ramadhani; Assyifa’u Qolbiatu Atthoyibah; Dea Clara May Christin Sijabat; Gracia Tri Putri Br Ginting; Ivan Fadillah; Lisnawaty Simatupang; Moondra Zubir (Universitas Negeri Medan, 2025)
This study focuses on the development of a natural deodorant spray to address body odor caused by bacterial activity in sweat. The formulation utilizes alum, basil leaf extract, and lemon extract, all known for their antibacterial properties. Three formulations were evaluated: F1 (alum and basil extract), F2 (alum and lemon extract), and F3 (a combination of all three). The formulations underwent physical testing, pH analysis, clarity assessment, skin irritation evaluation, and fabric compatibility tests. Results indicated that F1 demonstrated stability in pH and clarity, F2 offered a superior aroma, and F3 exhibited the strongest antibacterial efficacy with a balanced fragrance. All formulations were found to be non-irritating and safe for use. The combination of these natural ingredients demonstrates significant potential for producing eco-friendly and consumer-safe deodorant spray products, highlighting their effectiveness in combating body odor while maintaining user comfort and environmental sustainability.